(untitled) (Baghdad Science Journal, 2024)
During a diazotization coupling reaction, an azo dye-ligand (H4L) was formed by combining 3-aminophenol and 2,4,6-trihydroxyacetophenone. This ligand was then allowed to react with several different metal ions (Mo (VI), Fe (III), Co (II), Cr (III), Ru (III) and Rh (III)), forming stable metal complexes with various geometries. The binding of the azo-dye group to the metal ions was detected through the M-N and M-O absorption bands in Fourier-transform-infrared, which indicated the involvement of nitrogen and oxygen. LC-MS spectra confirmed the molecular weights of the ligand and its complexes, and elemental analysis was also conducted. Electronic spectra were used to determine the geometries of the complexes. Furthermore, the thermal stability of some compounds and the existence of water molecules were detected using Differential Scanning Calorimetry (DSC) and Thermogravimetric analysis (TGA). The antioxidant effectiveness of these complexes was tested towards 2,2-Diphenyl-1-picrylhydrazyl (DPPH), a stable free radical that can be used to test the radical scavenging activity of reactive oxygen species. The order of inhibitory action of the ligand H4L and its minerals towards reactive oxygen species was determined to be (H4L > Ascorbic acid > Mo-Complex > Fe-Complex > Cr-Complex > Rh-Complex > Ru-Complex) at 30 minutes. The DPPH test involves reducing the odd electron of a nitrogen atom by receiving a hydrogen atom from antioxidants to form the corresponding hydrazine. The results of the test varied between effective and ineffective inhibition values, as described in the manuscript.